Forest and Land Fires: A Perspectives on Peatland Ecosystem Protection Management in Jambi Province - Dwi Nanto (JURNAL KUASA, 2025)
Forest and land fires has had impact in the degradation of environmental conditions, human health, socio-economic conditions, and increased carbon emissions on the earth's surface. The phenomenon of Karhutla occurs almost every year in Jambi. Inadequate protection management and destructive practices, such as peatland drainage, have caused a decline in the carrying capacity and resilience of the environment, leading to various ecological disasters such as forest and land fires in Jambi. This study aims to capture the events of forest and land fires in Jambi that occurred between 2015 and 2024. The data are gathered from a peat restoration monitoring by Wahana Lingkungan Hidup Indonesia [WALHI] 2019-2020, Jambi Government, media information, and Peat Restoration Agency (BRG). The result of this study show that there are many peatland restoration projects carried out by companies do not comply with government regulations. Consequently, the peatland fires demonstrate a weak law enforcement effort and the failure of peatland restoration. From a political ecology perspective, the failure of peatland restoration reflects unequal power relations between the state, corporations, and local communities, where weak governance and profit-oriented policies undermine environmental justice and sustainability. Therefore, prevention through a political policy and political ecplogy are very essential.